Integrasi Teknologi dalam Pembelajaran Pendidikan Agama Islam: Peluang dan Tantangan - Aripin, Abdul Malik; Noviani, Dwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article examines the integration of technology in Islamic Religious Education (PAI) learning in the digital era. This study uses a literature study method to analyze the opportunities and challenges faced in integrating technology into the PAI curriculum. The results of the study indicate that technology integration can improve the effectiveness of PAI learning, but also requires a careful approach to ensure that Islamic values are maintained.